2020
DOI: 10.1038/s41436-019-0642-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric genomics researchers’ perspectives on best practices for returning results to individual participants

Abstract: Purpose: Large-scale array-based and sequencing studies have advanced our understanding of the genetic architecture of psychiatric disorders, but also increased the potential to generate an exponentially larger amount of clinically relevant findings. As genomic testing becomes more widespread in psychiatry research, urgency grows to establish best practices for offering return of results (RoR) to individuals at risk or diagnosed with a psychiatric disorder. Methods:We interviewed an international sample (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Despite these unresolved issues and contradictory findings, a recent survey of psychiatric genetic researchers indicated that 85% of basic scientists were in favor of returning genotypic information in some type of capacity (Kostick et al, 2018;Kostick, Pereira, Brannan, Torgerson, & Lázaro-Muñoz, 2019). Therefore, it is important to understand the complex issues surrounding the return of genotypic information in order to ensure that translation of psychiatric genetic research into clinical practice maximizes possible benefits and minimizes potential harms.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these unresolved issues and contradictory findings, a recent survey of psychiatric genetic researchers indicated that 85% of basic scientists were in favor of returning genotypic information in some type of capacity (Kostick et al, 2018;Kostick, Pereira, Brannan, Torgerson, & Lázaro-Muñoz, 2019). Therefore, it is important to understand the complex issues surrounding the return of genotypic information in order to ensure that translation of psychiatric genetic research into clinical practice maximizes possible benefits and minimizes potential harms.…”
Section: Introductionmentioning
confidence: 99%
“…The survey was developed based on the extant literature and the results of a previous study in which we (GL-M, SP) interviewed 39 psychiatric genetics researchers from 17 countries about their perspectives toward returning genetic research results to individual participants [6,7]. Data were collected with five-point Likert items with response options from "strongly disagree" to "strongly agree" with a neutral midpoint ("neither agree nor disagree") with the exception of two items examining respondents' preference regarding which professional should return results and how (modality) results should be returned.…”
Section: Survey Measuresmentioning
confidence: 99%
“…In fact, most laboratories likely do not have clinicians qualified to disclose this information. Furthermore, previous research suggests that many psychiatric genetics researchers believe it is important to help ensure that patient-participants whose results reveal or confirm increased risk for a psychiatric disorder have access to care [7]. The lack of clinicians that could communicate the implications of findings on many projects and concern about follow-up care may explain why an unexpectedly high number of respondents agreed that patient-participant results should be returned through the participant's treating psychiatrist.…”
Section: Lack Of Infrastructurementioning
confidence: 99%
See 2 more Smart Citations